The importance of M694V mutation in systemic lupus erythematosus; implications for its role in neutrophil extracellular traps associated renal involvement - Fariba Mohebichamkhorami; Shirin Farivar; Mahmoud Rafieian Kopaei (Society of Diabetic Nephropathy Prevention, 2017)
Background: Systemic lupus erythematosus (SLE) is characterized by multisystem organ involvement. Enhanced neutrophil extracellular traps (NETs) formation and release as well as impaired clearance of NETs have been reported in SLE patients. Renal involvement is common in SLE which might be through deposition of immune complexes within the kidneys. M694V mutation is one of the hot spots of Mediterranean fever gene (MEFV). MEFV mutations have been previously reported in a number of auto-inflammatory and autoimmune diseases in Iranian patients. Objectives: This case-control study was aimed to evaluate the potential influences of M694V gene mutation in SLE disease and in development of renal involvement. Patients and Methods: Genotyping of 130 patients and 116 healthy controls was done for M694V mutation (rs61752717, c.2080A>G) using amplification refractory mutation system- polymerase chain reaction (ARMS-PCR) method. Results: Significant differences in the alleles and genotypes frequencies of M694V mutation between SLE patients and ethnically matched healthy controls were detected in this study (9.9% versus 2.4% P=0.000, OR [odds ratio]= 4.277, CI= 2.213-8.265). Furthermore a significant difference of renal involvement between M694V mutation carriers versus noncarriers (8.5% versus 10.4%, P=0.017, OR= 2.149, CI= 1.135- 4.072). Conclusions: The association between M694V mutation and SLE susceptibility was observed. Additionally, renal involvement was significant in SLE patients compared to controls. This finding probably is developed through NET-associated Dnase1 inhibition and maybe amyloidosis. This study may help to explain the nature of the inflammatory state in mutation carriers and assist to an accurate understanding of how it influences SLE pathogenesis.